EFFECTS OF DETOMIDINE AND MIDAZOLAM ADMINISTERED ALONE OR COMBINED, ON INDUCTION DOSE AND QUALITY OF PROPOFOL AND KETAMINE ANESTHESIA IN GOATS - M. Asif; M. A. Khan; H. Akbar; M. O. Omer (Journal of Animal and Plant Sciences, 2021)
Pre-anesthetic treatment directly affects dose of induction agents that may result in least complication due to low anesthesia intake. The study was designed to investigate the effects of detomidine and midazolam on induction dose and quality of propofol and ketamine anesthesia in goats. Twelve female goats were randomly divided into six groups comprising two animals each. Control group (A) received (Normal saline+ propofol @4.20±0.10 mg/kg). While, group B received (detomidine@15µg/kg+ propofol), C received (detomidine@15µg/kg+ ketamine), D received (midazolam@0.25mg/kg+ propofol), E received (midazolam @ 0.25mg/kg+ ketamine) and group F received combination of all (detomidine @7µg/kg+ midazolam @ 0.12mg/kg+ propofol+ ketamine). The degree of sedation and analgesia, induction dose, % age reduction in induction dose, anesthesia quality and clinico-physiological parameters were evaluated. Detomidine-midazolam when administered combined, followed by induction with combination of propofol-ketamine caused deep sedation and analgesia, maximum % age reduction in induction dose and increased duration of anesthesia that differed significantly (p≤0.05) from control and other treatment groups. Detomidine and midazolam when administered alone, followed by induction with propofol and ketamine caused mild sedation and analgesia, marked % age reduction in induction dose and increased duration of anesthesia that differed non significantly (p>0.05) from each other. The significant (p≤0.05) changes in heart rate & respiratory rate and non-significant (p>0.05) changes in rectal temperature were noticed in all groups. It is concluded that the combination of detomidine-midazolam-propofol-ketamine was found to be safe and economical for short surgical procedures in goat.
Keywords: Detomidine; midazolam; sedatives; propofol; ketamine; anesthetics; goat